Recombinant Production of Human Aquaporin-1 to an Exceptional High Membrane Density in Saccharomyces cerevisiae - Bomholt, Julie (Public Library of Science, 2013)

(untitled)
In the present paper we explored the capacity of yeast Saccharomyces cerevisiae as host for heterologous expression of human Aquaporin-1. Aquaporin-1 cDNA was expressed from a galactose inducible promoter situated on a plasmid with an adjustable copy number. Human Aquaporin-1 was C-terminally tagged with yeast enhanced GFP for quantification of functional expression, determination of sub-cellular localization, estimation of in vivo folding efficiency and establishment of a purification protocol. Aquaporin-1 was found to constitute 8.5 percent of total membrane protein content after expression at 15°C in a yeast host over-producing the Gal4p transcriptional activator and growth in amino acid supplemented minimal medium. In-gel fluorescence combined with western blotting showed that low accumulation of correctly folded recombinant Aquaporin-1 at 30°C was due to in vivo mal-folding. Reduction of the expression temperature to 15°C almost completely prevented Aquaporin-1 mal-folding. Bioimaging of live yeast cells revealed that recombinant Aquaporin-1 accumulated in the yeast plasma membrane. A detergent screen for solubilization revealed that CYMAL-5 was superior in solubilizing recombinant Aquaporin-1 and generated a monodisperse protein preparation. A single Ni-affinity chromatography step was used to obtain almost pure Aquaporin-1. Recombinant Aquaporin-1 produced in S. cerevisiae was not N-glycosylated in contrast to the protein found in human erythrocytes.